EDUCATIONAL VALUES OF CREATIVE TECHNICAL ASSIGNMENTS - MASTALERZ, Elżbieta (Trends in education, 2009)
This article is about main goals of technical education regarding forming of personality values during practical exercises. Their common recognition is confirm by pedagogical practice, though scientific research on this topic are not regularly conducted and documented; therefore, technical predispositions and skills in pupils cannot be rationally marked, neither can be their influence on personality formation in adolescent students.
Keywords: values; education; technical education.